Biogeography of wild Arachis: Assessing conservation status and setting future priorities - Jarvis, Andy; Ferguson, Morag E.; Williams, D.E.; Guarino, Luigi; Jones, Peter G.; Stalker, H.T.; Valls, JFM; Pittman, RN; Simpson, CE; Bramel-Cox, P.J. (2003)
The conservation status of wild Arachis spp. is not well characterized for its maintenance and possible future exploitation for the improvement of cultivated peanut, Arachis hypogaea L. Our objectives were to use 2175 georeferenced observations of wild peanut (Arachis spp.) to assess the conservation status of the genus and to prioritize biologically and geographically future conservation actions. Species distribution predictions were made on the basis of 36 climate variables, and these data were synthesized with land-use data to map the potential distribution of each species, and hence the species richness of the whole genus, excluding A. hypogea. hotspots of species richness were found in Mato Grosso around Cuiaba and Campo Grande in Brazil and around the Serra Geral de Goias, northeast of Brasilia. The current state of in situ conservation areas poorly represents wild peanut, with only 48 of the 2175 observations from National Parks. Several species were identified as being under threat of extinction. These included A. archeri Krapov. & W.C. Gregory, A. setinervosa Krapov. & W.C. Gregory, A. marginata Gardner, A. hatschbachii Krapov. & W.C. Gregory, A. appressipila Krapov. & W.C. Gregory, A. villosa Benth., A. cryptopotamica Krapov. & W.C. Gregory, A. helodes Martius ex Krapov. & Rigoni, A. magna W.C. Gregory & C.E. Simpson, and A. gracilis Krapov. & W.C. Gregory (identification based on highly restricted ranges and land-use pressures); and A. ipaensis Krapov. & W.C. Gregory, A. cruziana Krapov., W.C. Gregory & C.E. Simpson, A. williamsii Krapov. & W.C. Gregory, A. martii Handro, A. pietrarellii Krapov. & W.C. Gregory, A. vallsii Krapov. & W.C. Gregory, and A. monticola Krapov. & Rigoni (identification based on insufficient observations and land-use pressures). It is suggested that ex situ conservation efforts should focus on the area around Pedro Gomes (300 km southeast of Cuiaba), 170 km south along the planned road from Cuiaba to Corumba, and around San Jose de Chiquitos in Bolivia, where some of the species adapted to lower temperatures may be found.